1989
DOI: 10.1017/s0033291700024259
|View full text |Cite
|
Sign up to set email alerts
|

Use and abuse of khat(Catha edulis): a review of the distribution, pharmacology, side effects and a description of psychosis attributed to khat chewing

Abstract: SynopsisThere have been relatively few reported cases of psychosis due to khat usage despite its heavy consumption in certain East African and Arabian countries. Four cases have been reported in the UK. We report here on three further cases of psychotic reactions to this substance in Somalian males, and emphasize the need to be aware of khat as a potential substance of abuse, with both medical and psychiatric complications. The features of khat psychoses are described and the relationship to amphetamine and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 33 publications
2
88
0
Order By: Relevance
“…Not previously described, to our knowledge, was the association found with khat chewing. Khat (Catha edulis) is an evergreen tree which grows at high altitudes extending from East to Southern Africa, as well as Afghanistan, Yemen, and Madagascar (25). The chewing of khat is common in certain countries of East Africa and the Arabian peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Not previously described, to our knowledge, was the association found with khat chewing. Khat (Catha edulis) is an evergreen tree which grows at high altitudes extending from East to Southern Africa, as well as Afghanistan, Yemen, and Madagascar (25). The chewing of khat is common in certain countries of East Africa and the Arabian peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…A better source of information is the 20 up-to-date descriptions of cases of khat-induced brief psychotic episodes that are available in the medical literature (Alem & Shibre, 1997;Carothers, 1945;Critchlow & Seifert, 1987;Dhadphale et al, 1981;Giannini & Castellani, 1982;Gough & Cookson, 1984;Jager & Sireling, 1994;McLaren, 1987;Nielen, van der Heijden, Tuinier & Verhoeven, 2004;Pantelis, Hindler & Taylor, 1989;Yousef et al, 1995). All except one of the patients in these studies were male.…”
Section: (B) Can Khat Induce Clinically Relevant Short-lived Psychotmentioning
confidence: 99%
“…A frequently reported pattern of khat use among these cases was solitary use, in contrast to the traditional social use. Pantelis et al (1989) reviewed 12 of these cases and identified three types with different symptom clusters: (1) The most common type was a paranoid psychotic state, often associated with auditory hallucinations and clear consciousness. (2) Others showed manic symptoms associated with grandiose delusions.…”
Section: (B) Can Khat Induce Clinically Relevant Short-lived Psychotmentioning
confidence: 99%
“…Furthermore, many commonly ingested substances can cause auditory hallucinations. In addition to intentional hallucinogens (such as LSD [Miller & Gold, 1994]), causal agents include psychiatric medications (benzodiazapines [Chinisci, 1985], imipramine [Terao, 1995]), other medications (pentoxifylline [Gilbert, 1993], propranolol [Fernandez, Crowther & Vieweg, 1998]), drugs of abuse (methamphetamine [Matsuoka, Yokoyama & Yamauchi, 1996], ecstacy [Miller & Gold, 1994], cocaine [Siegel, 1978]), and traditional medicinal plants (datura [Goates & Escobar, 1992], khat [Pantelis, Hindler & Taylor, 1989], mabi bark tea [Hassiotis & Taylor, 1992]). Some substances produce tinnitus first, suggesting a similar mechanism to that involved in deafness-precipitated auditory hallucinations.…”
Section: Situational Stressmentioning
confidence: 99%